Pentingnya Disiplin Kerja, Lingkungan Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan - Jonathan Jonathan; Ina Namora Putri Siregar; Cindy Fantika; Khairani Alawiyah Matondang (IPM2KPE, 2023)
This research aims to work discipline, work environment and job satisfaction on employee job performance. The research method used is quantitative. The results of the research show that partially Work Discipline has a positive and significant effect on the Work Performance of Employees, partially the Work Environment has a positive and significant effect on the Work Performance of Employees, partially Job Satisfaction has a positive and significant effect on the Work Performance of Employees and simultaneously Work Discipline, Work Environment and Job satisfaction has a positive and significant effect on employee job performance. The conclusion is that the important role of work discipline, work environment and job satisfaction is to improve employee work performance. Keywords: Discipline, Satisfaction, Environment, Work Performance